Waking up to antibiotic resistance - Wasim Kamate; Nupura Vibhute; Uzma Iqbal Belgaumi; Vidya Kadashetti (Journal of Pharmacy and Bioallied Sciences, 2023)
Background: Antimicrobial resistance (AMR) has emerged as a global concern, particularly in developing countries where its causes seem to entrench the knowledge, attitude, and practice of healthcare professionals and patients toward the use of antimicrobials. Methods: This review aims to provide a compendious yet thorough overview of our understanding of antibiotic resistance pertaining to dentistry. Literature provides evidence of inadequate antibiotic prescribing practices by dental professionals. Considering the growing concern about antibiotic prescribing habits and patient's tendencies of improper use, we attempt to address the interventional efforts of dentists and patients in the context to focus on the root causes specifically to prevention of the antimicrobial resistance. Results: Following the guidelines and flowchart depicted in this article, the members of dental professions will get clear views on the use of antibiotics. This will cause a definite decrease in the growing concern about antibiotic resistance.